Ore Deposits Of The Western States – Historical Review Of Geology As Related To Western Mining - F. L. Ransome (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1933)
THAT geology and mining should stand in close and mutually helpful relationship was recognized in the United States at an early period, but it is not possible to set a precise date at which the study of ore deposits became a thoroughly reputable and important branch of geological science. As early as 1850, appeared the first ,part of Foster and Whitney's report1 on the Lake Superior region, devoted mainly to the copper-bearing areas, followed, in the succeeding year, by the second part,2 on the iron lands. This appears to have been the first comprehensive report on what might, at that time at least, be called "western" ore deposits to be prepared and published under the auspices of the Federal government. An outgrowth from this work was Whitney's Metallic Wealth of the United States,3 which appeared in 1854. It was the earliest general work on the ore deposits of the country, and remained a standard reference book for marly forty years. From 1853 on, various parties were sent out by the War Department to explore routes for proposed railways and wagon roads from the Mississippi Valley to the Pacific Coast. Geologists were attached to most of these parties, but their work was mainly of broad reconnaissance character, little attention being paid to ore deposits. Although the